In Vitro and in Silico Evidence of Phosphatase Diversity in the Biomineralizing Bacterium Ramlibacter tataouinensis - Skouri-Panet, Fériel; Benzerara, Karim; Cosmidis, Julie; Férard, Céline; Caumes, Géraldine; De Luca, Gilles; Heulin, Thierry; Duprat, Elodie (Frontiers in Microbiology, 2018)
Microbial phosphatase activity can trigger the precipitation of metal-phosphate minerals, a process called phosphatogenesis with global geochemical and environmental implications. An increasing diversity of phosphatases expressed by diverse microorganisms has been evidenced in various environments. However, it is challenging to link the functional properties of genomic repertoires of phosphatases with the phosphatogenesis capabilities of microorganisms. Here, we studied the betaproteobacterium Ramlibacter tataouinensis (Rta), known to biomineralize Ca-phosphates in the environment and the laboratory. We investigated the functional repertoire of this biomineralization process at the cell, genome and molecular level. Based on a mineralization assay, Rta is shown to hydrolyse the phosphoester bonds of a wide range of organic P molecules. Accordingly, its genome has an unusually high diversity of phosphatases: five genes belonging to two non-homologous families, phoD and phoX, were detected. These genes showed diverse predicted cis-regulatory elements. Moreover, they encoded proteins with diverse structural properties according to molecular models. Heterologously expressed PhoD and PhoX in Escherichia coli had different profiles of substrate hydrolysis. As evidenced for Rta cells, recombinant E. coli cells induced the precipitation of Ca-phosphate mineral phases, identified as poorly crystalline hydroxyapatite. The phosphatase genomic repertoire of Rta was previously evidenced as prevalent in marine oligotrophic environments. Interestingly, the Tatahouine sand from which Rta was isolated showed similar P-depleted, but Ca-rich conditions. Overall, the diversity of phosphatases in Rta allows the hydrolysis of a broad range of organic P substrates and therefore the release of orthophosphates (inorganic phosphate) under diverse trophic conditions. Since the release of orthophosphates is key to the achievement of high saturation levels with respect to hydroxyapatite and the induction of phosphatogenesis, Rta appears as a particularly efficient driver of this process as shown experimentally.